Corporate social responsibility and organizational citizenship behavior: Mediating role of psychological capital, affective commitment, and prosocial motivation - Maharani, Ghina Syukriya; Rachmawati, Riani; Khan, Muhammad Khalil (Jurnal Fokus Manajemen Bisnis, 2025)
This research attempts to investigate the mechanisms linking corporate social responsibility with organizational citizenship behavior among Generation Z employees in Indonesia's banking sector, focusing on the mediating roles of psychological capital, affective commitment, and prosocial motivation. While Generation Z demonstrates high concern for social and environmental issues, paradoxically, they exhibit the lowest levels of organizational citizenship behavior among all generations. Data were collected through an online survey of 230 Generation Z employees in the Indonesian banking sector who had worked for at least 6 months. The study employs Covariance-Based Structural Equation Modeling for data analysis. The findings reveal that corporate social responsibility positively influence organizational citizenship behavior through the mediation of psychological capital, affective commitment, and prosocial motivation. These findings provide insights for banking institutions in designing effective corporate social responsibility strategies to enhance organizational citizenship behavior among Generation Z employees, while contributing to the literature by explaining the psychological mechanisms linking corporate social responsibility to organizational citizenship behavior. Practical and theoretical implications are discussed, along with suggestions for future research.